Duncan Liddel (1561-1613): networks of polymathy and the Northern European Renaissance - Omodeo, Pietro Daniel; Friedrich, Karin (Scientific and learned cultures and their institutions, 2016)
"This collective volume in the history of early-modern science and medicine investigates the transfer of knowledge between Germany and Scotland focusing on the Scottish mathematician and physician Duncan Liddel of Aberdeen. It offers a contextualized study of his life and work in the cultural and institutional frame of the northern European Renaissance, as well as a reconstruction of his scholarly networks and of the scientific debates in the time of post-Copernican astronomy, Melanchthonian humanism and Paracelsian controversies. Contributors are: Sabine Bertram, Duncan Cockburn, Laura Di Giammatteo, Mordechai Feingold, Karin Friedrich, Elizabeth Harding, John Henry, Richard Kirwan, Jane Pirie, Jonathan Regier"--